Perceptions of service quality, customer satisfaction and customer loyalty in mobile telephony in South Africa - Munsamy, Theesen (My University, 2011)
The South African mobile telephony sector is reaching saturation and churn rates are extremely high. The market is becoming more competitive with the advent of fixed mobile convergence, disruptive technologies and deregulation of the sector. Faced with all these challenges operators need to identify ways to keep customers loyal while ensuring that subscribers continue to increase their spending. The purpose of this paper is to investigate the crucial factors that lead to customer loyalty in the South African mobile telephony sector, namely service quality and customer satisfaction. Furthermore the antecedents, mediating and consequent relationships of customer loyalty, service quality and customer satisfaction was also examined. Data was obtained from 168 mobile phone users from the three MNO’s (mobile network operators) using a survey compiled from existing literature. The survey was confined to the Gauteng province. The data was analysed using structural equation modelling in order to test the relationships between the constructs. The findings support the proposed hypotheses and are consistent with other literary studies. Pricing, value added services and customer support services are the most significant service quality dimensions influencing customer satisfaction. Customer satisfaction has a direct positive impact on customer loyalty. Customer satisfaction was found to be the mediator between service quality and customer loyalty
MBA thesis - WBS
Keywords: Service quality; Customer satisfaction; Consumer behaviour; Mobile telephony; Mobile phones; Cell phones